Dry skin and pressure ulcer risk: A multi-center cross-sectional prevalence study in German hospitals and nursing homes. (August 2017) - Lechner, Anna; Lahmann, Nils; Neumann, Konrad; Blume-Peytavi, Ulrike; Kottner, Jan
Abstract: Background: Pressure ulcers are a serious health problem in medical and nursing care. Therefore, effective prevention is crucial. Major pressure ulcer risk factors have been identified but the particular role of dry skin (xerosis cutis) is unclear. Objectives: To investigate possible associations between dry skin and pressure ulcers focusing on the sacrum/trochanter and at heel/ankle skin areas. Design: Two multicenter cross-sectional studies. Settings/participants: In 2014 and 2015 thirty nursing homes and thirteen hospitals in Germany participated. In total 3837 participants were included. Mean age was 76.1 (SD 15.5) years. Methods: Skin assessments and data collection were performed by trained nurses based on a standardized data collection form. Descriptive comparisons and multilevel logistic regressions predicting pressure ulcers at sacrum/trochanter and ankle/heel were conducted. Results: The prevalence of skin dryness at the trunk was significantly higher for subjects with pressure ulcers category 2+ at the sacral area compared to without (39.0% vs. 24.4%, p = 0.010). Adjusted to demographic variables, mobility and type of institution dry skin at the trunk was no longer associated with pressure ulceration (OR 1.11 (95% CI 0.62–2.00)). 71.9% of patients with heel/ankle pressure ulcers category 2+ were affected by dry skin at legs or feet, compared to 42.8% of subjects without pressure ulcers (p < 0.001). In the adjusted analysis the OR was 1.85 (95% CI 0.83–4.14). Conclusions: Study results indicate that dry skin at the feet may be considered as a risk factor for heel pressure ulcer development. Skin dryness may be less important for sacral pressure ulcers. Therefore, the variable skin status should be better defined in future studies and pressure ulcer risk models. Results further support differences in pressure ulcer aetiologies between anatomical locations.